Tracing the Traces of Khairiyyah Hasyim: Education, Life and Stories of Indonesian Women Ulama (1906-1983 AD) - Badrah Uyuni; Mohammad Adnan (EDUJAVARE: International Journal of Educational Research, 2023)
This research explores the contribution of the da'wah of Indonesian female cleric Khairiyyah Hasyim (1906-1983 AD). This study aims to highlight Khairiyyah Hasyim's example so that women today can take inspiration and examples from the work and struggle of this female cleric for the progress of society, especially women. This research method uses a qualitative approach by examining various sources such as books, academic research, videos, online sources, and historical documents. The collected data was analyzed using the explanatory method, where social phenomena are understood based on common sense logic using historical, anthropological, and sociological approaches. The research results show that Indonesian female scholars such as Khairiyyah Hasyim (1946 AD) have made significant contributions to da'wah, thus having an impact on various aspects of people's lives. They actively participate in taklim meetings and invest their resources and time to advance da'wah. With the support of family, students, and the community, they build da'wah facilities and dedicate their time to providing greater benefits.